Inhibition of skin development by overexpression of transforming growth factor beta 1 in the epidermis of transgenic mice. - Sellheyer, K (1993)
To assess the effect of transforming growth factor beta 1 on the skin in vivo, we have targeted its expression to the epidermis of transgenic mice. To ensure that active TGF-beta 1 was expressed, we used a porcine TGF-beta 1 cDNA with mutations of Cys-223-->Ser and Cys-225-->Ser, which allow constitutive activation. Mice expressing the mutant transforming growth factor beta 1 transgene exhibited a marked phenotype at birth. The skin was very shiny and tautly stretched. These animals were rigid and appeared to be restricted in their ability to move and breathe; death occurred within 24 hr. Histologically, the most prominent features of the skin were a compact orthohyperkeratosis and a reduction in the number of hair follicles. Pulse-labeling studies with 5-bromodeoxyuridine demonstrated a marked reduction in the number of replicating cells in the epidermis and hair follicles. Thus, the macro- and microscopic appearance of these mice, as well as their neonatal lethality, most likely result from inhibition of normal skin development and suppression of epithelial cell proliferation by the overexpression of transforming growth factor beta 1.